Developing Preservice Elementary School Teachers’ Beliefs and Practices through TBLT-Based Teacher Education - Kazuyoshi Sato; Tomoko Yago (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2022)
Although the Japanese government decided to make English a formal subject for fifth and sixth graders from 2020, there has been little discussion about how to prepare English teachers. In fact, Curtain and Dahlberg (2003) pointed out that lack of skillful teachers has been a serious issue in teaching foreign languages to elementary school students all over the world. Moreover, in the research on task-based language teaching (TBLT)† “the role of the teacher has received scant attention” (Van den Branden, 2016, p.164). This study attempts to reveal how Japanese university students who desire to be elementary school teachers transform their beliefs about English language teaching to young learners and develop their teaching skills through TBLT-based teacher education. Keywords: preservice teachers’ beliefs and practices, teacher development, TBLT, beliefs about language learning, beliefs about language teaching